The determinants of regional disparities in skill segregation: Evidence from a cross section of German regions - Friso Schlitte; Fabian Böttcher; Annekatrin Niebuhr; Javier Revilla Diez (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
Increasing inequality in qualification specific employment prospects characterises labour markets in most highly developed countries. Theoretical models suggest that in-plant skill segregation might matter for the polarisation of employment and wages. According to these models production technology and the educational level of the work force are important determinants of skill segregation. There are some studies that investigate the increasing in-plant skill segregation at the national level. However, since production technologies and skill structures are characterised by pronounced regional disparities, there are likely significant differences in the level of segregation between regions. But empirical evidence on corresponding regional inequalities is lacking. The objective of this analysis is to investigate regional disparities in skill segregation in Germany. Our findings point to marked disparities among German regions. Moreover, we analyse the determinants of these differences at the regional level. The results of a regression analysis indicate that the local endowment with human capital is an important determinant for the regional level of skill segregation. Furthermore, skill segregation is increasing in most areas during the period under consideration, which may lead to unfavourable labour-market conditions for low-skilled workers in corresponding regional labour markets.
Keywords: R11; J21; J24; 330; regional labour markets; skill segregation; human capital